2009
DOI: 10.1152/ajpheart.00938.2008
|View full text |Cite
|
Sign up to set email alerts
|

CRP is a novel ligand for the oxidized LDL receptor LOX-1

Abstract: C-reactive protein (CRP) is a risk factor for cardiovascular events and functions to amplify vascular inflammation through promoting endothelial dysfunction. Lectin-like oxidized low-density lipoprotein (oxLDL) receptor-1 (LOX-1) is the primary endothelial receptor for oxLDL, and both its expression and function are associated with vascular inflammation. As a scavenger receptor, LOX-1 is capable of binding to a variety of structurally unrelated ligands. Evidence is provided that demonstrates that CRP can act a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 30 publications
5
50
0
Order By: Relevance
“…Our data demonstrated that CRP enhanced the release of sLOX-1 from activated macrophages in vitro and increased circulating sLOX-1 levels in vivo, which agreed with previous studies showing sLOX-1 levels correlated signifi cantly with CRP levels in ACS patients ( 26 ). Recent studies have shown that CRP may act a ligand for LOX-1 and that the interaction of CRP with LOX-1 enhances endothelial infl ammation ( 27,28 ). Thus, when the CRP concentration reaches a high level, it may stimulate secretion of infl ammatory factors and directly impair endothelial function.…”
Section: Crp Regulated Slox-1 Release From Macrophages Derived From Psupporting
confidence: 92%
“…Our data demonstrated that CRP enhanced the release of sLOX-1 from activated macrophages in vitro and increased circulating sLOX-1 levels in vivo, which agreed with previous studies showing sLOX-1 levels correlated signifi cantly with CRP levels in ACS patients ( 26 ). Recent studies have shown that CRP may act a ligand for LOX-1 and that the interaction of CRP with LOX-1 enhances endothelial infl ammation ( 27,28 ). Thus, when the CRP concentration reaches a high level, it may stimulate secretion of infl ammatory factors and directly impair endothelial function.…”
Section: Crp Regulated Slox-1 Release From Macrophages Derived From Psupporting
confidence: 92%
“…In this study, we established a new rapid and sensitive AlphaScreen SureFire assay as a strategy for studying the pharmacology of GPR55. This method has been used to explore ligands of the cytokine receptors (30), LDL endothelial receptor (31), and potassium channel TREK-1 receptors (32) and to develop antagonists for other intracellular targets (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not find any significant differences in the expression on CD32 and CD64 in pulmonary vascular tissue from CTEPH and nonthromboembolic PH patients. It has recently been shown that CRP is also a ligand of LOX-1, the primary endothelial receptor for oxLDL [36]. Moreover, oxLDL induced ICAM-1 and VCAM-1 mRNA expression [36] and ET-1 secretion by human umbilical vein ECs [37].…”
Section: In Vitro Effects Of Crp On Pulmonary Vascular Cellsmentioning
confidence: 99%